Cinnamomi Cortex and Scutellariae Radix in the Japanese herbal medicine Kampo saireito inhibit expression of iNOS through different mechanisms in hepatocytes. Issue 1 (25th February 2020) - Matsushima, Hideyuki; Hishikawa, Hidehiko; Miki, Hirokazu; Hatta, Masahiko; Nakatake, Richi; Okumura, Tadayoshi; Nishizawa, Mikio; Kaibori, Masaki; Sekimoto, Mitsugu
ABSTRACT: Aim: The Japanese herbal medicine, saireito, prevents the induction of inducible nitric oxide synthase (iNOS) expression and NO production, which is an indicator of liver protection. Saireito is composed of 12 kinds of crude drug. This study aimed to examine whether these crude drugs influence the induction of iNOS gene expression and if so, the mechanisms involved. Methods: Hepatocytes were isolated from rats by collagenase perfusion and cultured. Each crude drug was added to primary cultured cells stimulated by interleukin (IL)‐1β. Induction of iNOS/NO production and its signaling pathway were analyzed. Results: IL‐1β induced iNOS expression and NO production. Eleven of the saireito crude drugs inhibited NO production. Among them, Cinnamomi Cortex and Scutellariae Radix had higher effects than the others and inhibited the expression of iNOS and tumor necrosis factor (TNF)‐α. Transfection experiments revealed that both crude drugs reduced the activities of iNOS promoter transactivation (mRNA synthesis) and its mRNA stability. However, Cinnamomi Cortex and Scutellariae Radix showed that different mechanisms were involved in their inhibitory effects on two signaling pathways of iNOS induction, IκBα degradation/nuclear factor (NF)‐κB activation and Akt activation/type I IL‐1 receptor (IL‐1RI) upregulation. Conclusion: Cinnamomi Cortex and Scutellariae Radix can prevent the induction of iNOS gene expression, in part through NF‐κB activation and IL‐1RI upregulation with different mechanisms, indicating that saireito containing both crude drugs may be a potential therapeutic treatment for injured livers.